Do More Tourists Promote Local Employment? - Libertad González; Tetyana Surovtseva (Institute of Labor Economics (IZA), 2024)
We analyze the impact of tourist flows on local labor markets, following a novel identification strategy that uses temporary shocks in alternative international destinations to instrument for tourism flows across Spanish regions. We find that a one standard deviation increase in tourist inflows leads to a 1 percentage-point increase in employment in the tourism industry and in other services, but it does not increase total employment, labor force participation, or wages in local economies. Instead, the positive impact on services is compensated by a fall in employment in other industries, most notably manufacturing.
Keywords: J21; 330; employment; tourism; local labor markets; shift-share; terrorism; Spain